Evaluation of nitrogen fixation potential of cowpea varieties and effect of residue nitrogen for maize production - Fataah, Juliana (2016)
A thesis submitted to the Department of Crop and Soil Sciences, Faculty of Agriculture of the College of Agriculture And Natural Resources, Kwame Nkrumah University of Science and Technology, Kumasi, Ghana. This is in partial fulfillment of the requirement for the award of M.Phil. in Agronomy (Crop Physiology).